Fiscal Resilience and Defense Financing Innovation for Sustainable National Security Post Ukraine–Russia War - Aris Marsudiyanto; Athor Subroto; Bambang Permadi Soemantri Brodjonegoro; A. Hanief Saha Ghafur (Proceedings of International Conference on Science, Education, and Technology, 2025)
Global geopolitical escalation following the Ukraine–Russia conflict intensifies fiscal and security pressures across many regions, including Indonesia. Long-horizon macroeconomic evaluation demonstrates persistent structural limitations marked by slow revenue elasticity, recurring deficits, exchange-rate exposure, and rising debt-service commitments, all of which reduce flexibility for long-term defense modernization. Geopolitical disturbances amplify those constraints through elevated global military expenditure, higher procurement costs, and expanding cyber, maritime, and hybrid threats within the Indo-Pacific region. Sectoral vulnerabilities further weaken strategic readiness, particularly due to import dependency, limited domestic industrial capability, and increasing operational expenditure. Institutional rigidity also limits adoption of innovative financing mechanisms capable of supporting multi-source and multi-year commitments. Integrated analysis indicates the need for diversified financing pathways that reduce exposure to external shocks and enhance the predictability of defense investment. Potential strategies include defense-industry reinvestment, public-asset monetization, public–private partnerships, and hybrid financing frameworks aligned with long-term capability requirements. Sustainable security therefore depends on structural fiscal reform, institutional modernization, and coordinated integration of fiscal, security, and industrial policy to strengthen Indonesia’s strategic resilience in an increasingly volatile geopolitical landscape.